Step
*
2
1
of Lemma
extend-name-morph-comp
1. I : Cname List
2. J : Cname List
3. K : Cname List
4. f : name-morph(I;J)
5. g : name-morph(J;K)
6. z : Cname
7. v : Cname
8. v1 : Cname
9. ¬(z ∈ I)
10. ¬(v ∈ K)
11. ¬(v1 ∈ J)
12. x : nameset([z / I])
13. ¬(x = z ∈ Cname)
14. x ∈ nameset(I)
15. ↑isname(f x)
⊢ (g (f x)) = if eq-cname(f x;v1) then v else g (f x) fi  ∈ extd-nameset([v / K])
BY
{ (FLemma `assert-isname` [-1] THENA Auto) }
1
1. I : Cname List
2. J : Cname List
3. K : Cname List
4. f : name-morph(I;J)
5. g : name-morph(J;K)
6. z : Cname
7. v : Cname
8. v1 : Cname
9. ¬(z ∈ I)
10. ¬(v ∈ K)
11. ¬(v1 ∈ J)
12. x : nameset([z / I])
13. ¬(x = z ∈ Cname)
14. x ∈ nameset(I)
15. ↑isname(f x)
16. f x ∈ nameset(J)
⊢ (g (f x)) = if eq-cname(f x;v1) then v else g (f x) fi  ∈ extd-nameset([v / K])
Latex:
Latex:
1.  I  :  Cname  List
2.  J  :  Cname  List
3.  K  :  Cname  List
4.  f  :  name-morph(I;J)
5.  g  :  name-morph(J;K)
6.  z  :  Cname
7.  v  :  Cname
8.  v1  :  Cname
9.  \mneg{}(z  \mmember{}  I)
10.  \mneg{}(v  \mmember{}  K)
11.  \mneg{}(v1  \mmember{}  J)
12.  x  :  nameset([z  /  I])
13.  \mneg{}(x  =  z)
14.  x  \mmember{}  nameset(I)
15.  \muparrow{}isname(f  x)
\mvdash{}  (g  (f  x))  =  if  eq-cname(f  x;v1)  then  v  else  g  (f  x)  fi 
By
Latex:
(FLemma  `assert-isname`  [-1]  THENA  Auto)
Home
Index